Dialektika al-Qur’an dalam al-Urf: Studi Kritis Pergeseran Makna Budaya Mappasikarawa pada Perkawinan Bugis di Era Modern - Sunuwati; Hasnani; Aris; Abdullah, Baharuddin; Darwis, Rizal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study examines the transformation of meaning in the Bugis society’s mappasikarawa culture, which has undergone significant shifts in values due to modernity. It employs a dialectical approach between the Qur’an and local cultural context as al-urf to map the dynamic relationship between universal Islamic values and local wisdom. Using a qualitative analytical-critical method, data was gathered through in-depth interviews, participant observation, and document analysis in Bugis regions. Findings show that mappasikarawa serves not only as a symbolic ritual but also integrates Qur’anic values sakinah, mawaddah, and rahmah. Thus, a contextual reinterpretation based on maqaṣid al-shariah and hifz al-nafs is essential to maintain its relevance and harmony with Islamic law.